2010
DOI: 10.1021/ja102623j
|View full text |Cite
|
Sign up to set email alerts
|

Total Synthesis and Biological Evaluation of the Resveratrol-Derived Polyphenol Natural Products Hopeanol and Hopeahainol A

Abstract: The total synthesis and biological evaluation of the resveratrol-derived natural products hopeanol (2) and hopeahainol A (3) in their racemic and antipodal forms are described. The Friedel-Crafts-based synthetic strategy employed was developed from model studies that established the feasibility of constructing the C(7b) quaternary center through an intramolecular Friedel-Crafts reaction and a Grob-type fragmentation to introduce an obligatory olefinic bond in the growing molecule. The final stages of the synth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
69
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(70 citation statements)
references
References 38 publications
0
69
0
1
Order By: Relevance
“…27 By contrast, wholly stepwise, non-biomimetic sequences empowered by retrosynthetic analysis can produce single dimeric members with control, but do not possess the strategic power to deliver a family-level solution for all frameworks. 5,6,28,29,30,31 Herein, we establish an approach with the potential to lead to the entire resveratrol collection controllably, one member at a time.…”
mentioning
confidence: 99%
“…27 By contrast, wholly stepwise, non-biomimetic sequences empowered by retrosynthetic analysis can produce single dimeric members with control, but do not possess the strategic power to deliver a family-level solution for all frameworks. 5,6,28,29,30,31 Herein, we establish an approach with the potential to lead to the entire resveratrol collection controllably, one member at a time.…”
mentioning
confidence: 99%
“…2A). The absolute ( S )- or (+)-configuration of naturally occurring hopeahainol A has been inferred from molecular modeling and the crystal structure of permethylated hopeahainol A (where four phenolic hydroxyl groups are methylated) [23, 29]. Our preliminary molecular modeling indicated that hopeahainol A is too bulky to be accommodated within the long but narrow AChE active site gorge without severe distortion of the gorge as depicted in AChE crystal structures.…”
Section: Resultsmentioning
confidence: 97%
“…Basic methanol is known to convert hopeahainol A to hopeanol through methanolysis of the χ-lactone moiety [24, 29], and incubation of hopeahainol A here in 3 mM NaPi (pH 7.0) gave UV spectral changes consistent with conversion to hopeanol [23] over a 2-day period. Hopeanol is reported to have no inhibitory activity with AChE [23, 29]. …”
Section: Resultsmentioning
confidence: 99%
“…The final step in AFS catalysis is reminiscent (although not identical) to intramolecular Friedel-Crafts reactions reported in the literature. 78 Biosynthesis of farnesene serves as an excellent example of how enzymes use allylic carbocation chemistry to conduct different chemical transformations which are not unfamiliar in the world of synthetic organic chemistry.…”
Section: Discussion Of Chemical Insightsmentioning
confidence: 99%